Recent developments in understanding mast seeding in relation to dynamics of carbon and nitrogen resources in temperate trees. Issue 6 (30th August 2017) - Han, Qingmin; Kabeya, Daisuke
Abstract: Mast seeding, the synchronous intermittent production of large seed crops in populations of perennial plants, is a widespread and widely studied phenomenon. Economy of scale has been demonstrated to provide the ultimate selection factor driving the evolution of masting, for example, in terms of the predator‐satiation and pollination‐efficiency hypotheses; however, its physiological mechanism is still poorly understood. The resource budget (RB) model assumes that an individual plant requires more resources to flower and fruit than it gains in a year, and therefore only flowers when a specific threshold amount of stored resources is surpassed. Although the RB models have been well explored theoretically, including for resource depletion and pollen coupling, empirical data to support these assumptions are still disputed. Here, we explore the extent to which the RB model applies to masting tree species, focusing on the dynamics of carbon and nitrogen resources in natural temperate forests. There is little empirical evidence that plants use carbohydrates stored over several years to produce fruits; however, nitrogen stores in temperate trees are more commonly depleted after masting. We review the internal nitrogen cycle including resorption during leaf senescence, storage and remobilization, discussing the effect of masting on these processes. Overall, carbohydrates and nitrogen are clearly involved in the proximate mechanisms driving mast seeding, but the determinant resource seems to be species specific.